Fenomena Hydraulic Jump Look Like Dan Onset Of Flooding Dalam Pipa Vetikal - M Mahmuddin; Samsul Kamal; Indarto Indarto; P Purnomo (Department Industrial Engineering, University of Muhammadiyah Malang, 2011)
Experiments have been conducted on countercurrent flow of air and water in pipe of 24 mm diameter. Flow patterns observations, measurement of the pressure gradient and film thickness conducted at water Reynolds numbers (ReL) are varied 322, 465, 630 and 709 combined to injected air with velocity from 1.845 m/s to 6.148 m/s at a distance of 400 mm, 1600 mm and 2200 mm from the water inlet. The data showed that the pressure gradient and film thickness did not increase appreciably until just before the onset of flooding. Otherwise, when flooding conditions wave propagation in surface the film flow from the bottom of air inlet, increasing film thickness gradually and pressure gradient also increase quickly. Increasing film thikcness gradually indicated as phenomenon hydraulic jump look like.